Too bad to benefit? Effect heterogeneity of public training programs - Ulf Rinne; Marc Schneider; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2007)
This study analyzes the treatment effects of public training programs for the unemployed in Germany. Based on propensity score matching methods we extend the picture that has been sketched in previous studies by estimating treatment effects of medium-term programs for different sub-groups with respect to vocational education and age. Our results indicate that program participation has a positive impact on employment probabilities for all sub-groups. Participants also seem to find more often higher paid jobs than non-participants. However, we find only little evidence for the presence of heterogeneous treatment effects, and the magnitude of the differences is quite small. Our results are thus at least in part conflicting with the strategy to increasingly provide training to individuals with better employment prospects.
Keywords: J64; 330; Program evaluation; active labor market policy; effect heterogeneity; public training programs; matching; Arbeitsmarktpolitik; Weiterbildung; Wirkungsanalyse; Beschäftigungseffekt; Deutschland